2003
DOI: 10.1264/jsme2.18.105
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Dioxin-Degrading Microorganisms and Potential Utilization in Bioremediation.

Abstract: Dioxins are a group of chloroaromatic compounds known to be toxic and carcinogenic, and persistent environmental pollutants. How to remedy dioxin-polluted environments is one of the most challenging problems in environmental technology. From ecological and economical viewpoints, biological methods using particular microorganisms and microbial consortia capable of dioxin transformation and degradation have greater appeal than physicochemical methods in their application for environmental remediation. Large numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 207 publications
(120 reference statements)
1
61
0
7
Order By: Relevance
“…These chloroaromatics possibly undergo microbial breakdown as well as physicochemical degradation in the environment, as a number of studies have demonstrated the existence of a wide variety of dioxintransforming microorganisms 23,56) . However, information about the effects of microbial activity on the fate and dynamics of dioxins in contaminated areas is still scanty.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These chloroaromatics possibly undergo microbial breakdown as well as physicochemical degradation in the environment, as a number of studies have demonstrated the existence of a wide variety of dioxintransforming microorganisms 23,56) . However, information about the effects of microbial activity on the fate and dynamics of dioxins in contaminated areas is still scanty.…”
mentioning
confidence: 99%
“…In recent years, microbial reductive dechlorination of PCDD/Fs and PCBs has received intensive study, because this biological activity is not only possibly the initial step in the biotransformation of organohalorides in the environment but also has important implications for engineered bioremediation 1,23,43,56) . Microbial dechlorination of PCDD/ Fs has been demonstrated in studies of anaerobic microcosms using contaminated sediment and soil 2,[7][8][9]12,20,31,49,52) .…”
mentioning
confidence: 99%
“…NhiÒu vi khuÈn thuéc líp nµy cã kh ¶ n¨ng sö dông 2,4-D, 2,4,5-T, dioxin vµ c¸c hîp chÊt t−¬ng tù [2,3]. KÕt qu ¶ trong ®ît kh ¶o s¸t nµy còng phï hîp víi mét sè ph¸t hiÖn cña c¸c t¸c gi ¶ kh¸c vÒ ®a d¹ng vi sinh vËt trong ®Êt nhiÔm chÊt diÖt cá [11] vµ polychlorinated biphenyl (d¹ng hîp chÊt cã cÊu tróc t−¬ng tù dioxin) [10].…”
Section: -15dn3-4unclassified
“…6,7) Chlorinated dioxins can be microbially degraded (for reviews, see refs. [8][9][10][11]. In general, degradation proceeds co-metabolically, and it is relatively slow for some congeners, especially of highly chlorinated dioxin.…”
Section: Functional Expression Of Three Rieske Non-heme Iron Oxygenasmentioning
confidence: 99%